Formulation of Goroho Banana (Musa acuminafé, sp) Wheat Flour and Tapioca Flour in The Making of Wheel Cakes - Jufrin Pagune; Asriani I.Laboko; Meilan Taguge (MultiTech Publisher, 2023)
The purpose of this research is to determine the effect of adding goroho banana flour, wheat flour and tapioca flour on texture, ash content and carbohydrate content as well on wheel cake products. This research method used a completely randomized design with 3 treatments and 3 times repetition, namely K1 = 100 g rice flour + 50 g wheat flour, K2 = 100 g rice flour + 50 g goroho banana flour and K3 = 100 g rice flour + 50 g tapioca flour. Parameters observed were texture analysis, ash content, and carbohydrate content as well as organoleptic tests. The results showed that the highest texture analysis was in treatment K1 (100 g rice flour + 50 g goroho banana flour) with a value of 3.12 kg and the lowest was in the K0 treatment (100 g rice flour + 50 g wheat flour) with a value of 2.74%. The highest ash content was in treatment K1 (100g rice flour + 50g goroho banana flour) with a value of 1.24% and the lowest was in treatment K2 (100g rice flour + 50g tapioca flour) with a value of 0.80%. The highest carbohydrate content was found in treatment K0 (100 g rice flour + 50 g wheat flour) with a value of 46.08% and the lowest in treatment K2 (100 g rice flour + 50 g tapioca flour) with a value of 44.68%.